2011
DOI: 10.1016/j.jns.2011.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of myosin-IIB in the brain of a rat model of streptozotocin-induced diabetes

Abstract: The Ca(2+)/calmodulin complex interacts with and regulates various enzymes and target proteins known as calmodulin-binding proteins (CaMBPs). This group of proteins includes molecular motors such as myosins. In this study, we show that non-muscle myosin-IIB is overexpressed in the brains of diabetic rats. We isolated CaMBPs from the brains of non-diabetic rats and rats with streptozotocin-induced diabetes and purified them by immobilized-calmodulin affinity chromatography. The proteins were eluted with EGTA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…Myosin-IIB modulates neurotransmitter release from synapses [83] while myosin-Va mediates synaptic vesicle trafficking [84]. We recently demonstrated that acute diabetes (20 days) alters protein and mRNA expression of myosin-IIB and myosin-Va in the rat brains [21, 23]. In the present study, we revealed an increased protein and mRNA expression of myosin-IIB and a decreased one of myosin-Va in chronic diabetic rat brains (90 days).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myosin-IIB modulates neurotransmitter release from synapses [83] while myosin-Va mediates synaptic vesicle trafficking [84]. We recently demonstrated that acute diabetes (20 days) alters protein and mRNA expression of myosin-IIB and myosin-Va in the rat brains [21, 23]. In the present study, we revealed an increased protein and mRNA expression of myosin-IIB and a decreased one of myosin-Va in chronic diabetic rat brains (90 days).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we revealed an increased protein and mRNA expression of myosin-IIB and a decreased one of myosin-Va in chronic diabetic rat brains (90 days). It is possible that these translational and transcriptional changes are due to low insulin level and high glucose level in circulation providing a possible dysfunction in vesicle/organelle movement [21, 23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One intriguing question that posits from these observations is that if myosin Va is an important regulator of both vesicular and non-vesicular neurotransmission in both the central and peripheral nervous system, how can neuronal physiological function continue to operate, albeit at a lower level of performance, despite reduction, or absence of myosin Va. One likely reason of how neurotransmission function is sustained in the face of diminished myosin Va may be due to neuroplastic changes. For example, it has been reported that in the brain, similar diabetic conditions that result in myosin Va reduction also results in increased expression of non-muscle myosin II (NMMII) ( 64 ). NMMII plays a critical role in vesicular neurotransmitter release at the cortex of the nerve terminal.…”
Section: Discussionmentioning
confidence: 99%
“…CALÁBRIA et al, 2011;DA COSTA et al, 2013). Os ratos não diabéticos receberam injeção do mesmo volume de tampão citrato, nas mesmas condições dos diabéticos induzidos.…”
unclassified